1998
DOI: 10.1332/030557398782025673
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion in Europe: paradigms of social disadvantage in Germany, Spain, Sweden and the United Kingdom

Abstract: English This article reviews contemporary discussions of the concept of social exclusion in Europe and examines different paradigms of inclusion and exclusion in selected European countries. A central concern of the article is to link the literature on social exclusion with the debate on welfare regimes and labour market structures and mechanisms of social protection. Drawing on recent comparative analyses the article also considers how women and ethnic minority groups, as well as different social classes, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…A marginalisation process is typically thought to involve a multiplicity of problems that interact in ways that make their total impact more harmful than suggested by simply adding them up. It is a process of 'losing ground' on a number of arenas simultaneously, such as the labour market, the social network, and the political and cultural life (Cousins, 1997;Fleming and Keenan, 2000). However, the former of these arenas is typically assumed to play a key role in marginalisation processes, and there is ample evidence that labour market marginality tends to spill over to other spheres of social life.…”
Section: Introductionmentioning
confidence: 99%
“…A marginalisation process is typically thought to involve a multiplicity of problems that interact in ways that make their total impact more harmful than suggested by simply adding them up. It is a process of 'losing ground' on a number of arenas simultaneously, such as the labour market, the social network, and the political and cultural life (Cousins, 1997;Fleming and Keenan, 2000). However, the former of these arenas is typically assumed to play a key role in marginalisation processes, and there is ample evidence that labour market marginality tends to spill over to other spheres of social life.…”
Section: Introductionmentioning
confidence: 99%
“…-social inclusion (Cousins, 1999), encompassing a sufficient level of access of farmers to provisions such as housing, income, health, labor and good working conditions, services, facilities, education and financial security; -identity, enabling a farmer to live according to his/her own values and norms, within the limits of pre-conditions postulated by the larger society; -social capital, referring to the diverse networks and relations of trust between people involved in agriculture. Social capital strengthens social cohesion and stability within groups of people, organizations or society at large.…”
Section: Translating a Vision Into Concrete And Relevant Themesmentioning
confidence: 99%
“…Although Silver cautioned that these should not be associated with a welfare state that is necessarily the product of competing and hybrid ideologies, Cousins (1998) has suggested that in the mid 20 th century Britain fitted the monopoly model before switching to the specialisation model in the 1980s. Arguably it is currently closer to the solidarity model with New Labour taking its lead from the European Union discourse on social exclusion.…”
Section: Shifting Policy Discourses: From Social Exclusion To Culturamentioning
confidence: 99%